God-Realisation through Multiple Religions? A Study into Religious Experiences of Sri Ramakrishna - AKRAM, MUHAMMAD (Islamic Studies, 2017)
Sri Ramakrishna (1836–1886) is an important Hindu spiritual personality from the nineteenth century Bengal who is best known for his pluralistic approach to religions, which is based on his claim to have practically experienced the same divine reality through various strands of Hinduism and different religions of the world. This paper pertains to an analytical survey of his religious experiences including his supposed conversions to Islam and Christianity. Without taking an outright reductionist approach to all of his religious experiences it is viewed that claims of God-realisation through Islam and Christianity seem problematic from the perspective of these religious traditions. However, there is no denying of the fact that Ramakrishna’s supposed realisation of God through various religions can definitively inculcate in Hindus (and others who endorse his experiences) a tolerant attitude and pluralist approach to different religions. To that extent Ramakrishna’s religious experiences can be conducive to peaceful interreligious coexistence and interfaith harmony.